2022
DOI: 10.4314/jopat.v21i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional composition of Phragmanthera incana (Schum) leaves selected from four host trees

Abstract: Phragmanthera incana (Schum) belonging to the family Loranthaceae, is a specie of mistletoe commonly found on trees in South-western part of Nigeria. They are hemi-parasitic plants that grow on trees which have been employed ethno-medicinally to treat several disease conditions. This study therefore evaluate the dietary and nutritional composition of the plant. Fresh leaves of P. incana from four host trees; Psidium guajava (guava), Cola acuminata (kolanut), Anacardium occidentale (cashew), and Mangifera indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The presence of heavy metals in some of the samples may be due to the poor disposal of solid waste, which contributes greatly to the degree of pollution in developing countries. The concentrations of metals in the selected water samples are within the permissible limit of USEPA (2022) and WHO (2017) ceruloplasmin (Adeyemi & Osilesi, 2022). All the values of heavy metals in this study are lower than those reported by Ogundele and Mekuleyi (2018), Kamaruzzaman et al (2011) andMortuza andAl-Misned (2017).…”
Section: Resultssupporting
confidence: 54%
“…The presence of heavy metals in some of the samples may be due to the poor disposal of solid waste, which contributes greatly to the degree of pollution in developing countries. The concentrations of metals in the selected water samples are within the permissible limit of USEPA (2022) and WHO (2017) ceruloplasmin (Adeyemi & Osilesi, 2022). All the values of heavy metals in this study are lower than those reported by Ogundele and Mekuleyi (2018), Kamaruzzaman et al (2011) andMortuza andAl-Misned (2017).…”
Section: Resultssupporting
confidence: 54%
“…The leaves have been used ethno-medicinally in the management of various diseases, such as hypertension, diabetes, insomnia, among others Ogunmefun et al, 2013). The leaves contain different bioactive compounds, such as flavonoids, terpenoids, alkaloids, saponins, tannins and are rich sources of dietary elements essential for biochemical processes and body metabolism (Adeyemi & Osilesi, 2022). They represent a family of plant species with an untapped reservoir of novel compounds for drug discoveries (Adeyemi & Osilesi 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The leaves contain different bioactive compounds, such as flavonoids, terpenoids, alkaloids, saponins, tannins and are rich sources of dietary elements essential for biochemical processes and body metabolism (Adeyemi & Osilesi, 2022). They represent a family of plant species with an untapped reservoir of novel compounds for drug discoveries (Adeyemi & Osilesi 2022). The inhibitory effect of methanol extract of P. incana leaves harvested from Kolanut and Cocoa on Fe 2+ induced lipid peroxidation and a higher radical scavenging abilities (Ogunmefun et al, 2015).…”
Section: Introductionmentioning
confidence: 99%